Orpheus XXI, Musique pour la vie et la dignité : Un film documentaire - Rudant, Manon Louise; Savall, Jordi 1941-
A film by Manon Louise Rudant. Under the artistic management of Jordi Savall, “ORPHEUS XXI – Music for life and dignity” is an artistic and educational action plan, designed as a replicable learning platform, for the integration of young refugees with musical knowledge or talent.
Keywords: Music education